Bioresponsive polymeric nanotherapeutics for targeted cancer chemotherapy. Issue 5 (October 2015) - Cheng, Ru; Meng, Fenghua; Deng, Chao; Zhong, Zhiyuan
Graphical abstract: Highlights: Gives an overview on biosignals existing in the tumor and tumor cells. Illustrates the potential impacts and uses of biosignals on anticancer drug delivery. Highlights the design rationale and recent exciting development of bioresponsive polymeric nanotherapeutics for targeted cancer chemotherapy. Presents personal perspectives on the challenges and future development of translational nanomedicine based on bioresponsive polymeric nanotherapeutics. Summary: In recent years, bioresponsive polymeric nanotherapeutics that facilitate tumor cell uptake and trigger drug release at the target site have emerged as a fascinating platform for safe and efficient cancer therapy. The naturally occurring environments such as tumor acidity, tumor extracellular enzymes like matrix metalloproteases (MMP), endo/lysosomal pH, elevated glutathione levels in the cytoplasm and cell nucleus, lysosomal enzymes, as well as reactive oxygen species (ROS) in the mitochondria have been exploited as potential internal stimuli to achieve active drug and protein release in the tumor tissue or cancer cells. These bioresponsive nanosystems present several unique features such as no need of an external device, precision control over site of response (from tumor tissue down to cellular organelle level) following accumulation in the tumor via either passive or active targeting, and spontaneous activation in the tumor site or inside the tumor cells. In this review, we highlight the design rationale and recent exciting development of bioresponsive polymeric nanotherapeutics for enhanced cancer treatments with low side effects.